Development Of Light Weight Propeller Bracket - Mazlan, Mohamad Rukaini (Universiti Sains Malaysia, 2018)
The purpose of this thesis is to design, analyze and fabricate the light weight propeller bracket which is contributing to the stability of the Merlin light aircraft because the existing design are overweight. This problem cause the aircraft not stable during flight. This research is focus on the mass of CAM100 that are overweight due to the design of propeller bracket. The new design is made by using topology optimization from ANSYS software. The optimized structure is then converted into the truss element. Truss structures and space frame have been preferred solution to the problem of maximizing structural efficiency as they allow for very large increase in the flexural rigidity and load carrying capacity plus it has strength to weight ratio. The new design method such as truss element method and composite structure are used as new design for the structure which have weight reduction. The structure then is analyzed by using Finite element method and it is compared with analytical method to ensure there is no failure during engine operation. The best design then fabricated for truss element structure and composite material structure. The final weight reduction is taken to compare which has higher weight reduction The result show that new design has weight reduction which give aircraft more stability.